Effect of Alpha-Lipoic Acid and Vitamin E Supplementation on Oxidative Stress, Inflammation, and Malnutrition in Hemodialysis Patients (Iranian Journal of Kidney Diseases, 2013)
Introduction. Increased oxidative stress, inflammation, and malnutrition are present in hemodialysis patients and these factors exacerbate cardiovascular comorbidities. Vitamin E and α-lipoic acid (ALA) may have a protective role against cardiovascular disease risk factors via anti-oxidative and anti-inflammatory properties. The aim of this study was to evaluate the effect of ALA and vitamin E administration (alone or combined) on hemodialysis-induced stress oxidation, inflammation, and malnutrition. Materials and Methods. In a randomized placebo-controlled trial, we examined the effects of 2-month supplementation by vitamin E and ALA (alone or combined) on biomarkers of lipid peroxidation (malondialdehyde), inflammation (high-sensitivity C-Reactive protein and interleukin-6), and malnutrition (Subjective Global Assessment and body mass index) in 85 hemodialysis patients receiving ALA (600 mg), vitamin E (400 IU), ALA and vitamin E, and placebo. Results. After supplementation, no significant changes were observed in malondialdehyde level; however, there was a decrease in the ALA and vitamin E group during the period of the study.  Also, a nonsignificant decrease was seen in the high-sensitivity C-Reactive protein concentration of the interventional groups. Supplementation of vitamin E with and without ALA significantly reduced interleukin-6 concentration. A significant improvement was observed in malnutrition status of all groups. Conclusions. Vitamin E and ALA supplementation, especially their combination, might improve inflammation and malnutrition status, which suggest it as a potential preventive strategy against CVD among end-stage renal disease patients.